The influence of strongly turbulized liquid flow parameters on the near-wall transitional flows in the boundary layer - V.M. Zubarev (Учёные записки Казанского университета: Серия Физико-математические науки)
The effect of the scale and the high intensity of incident-flow turbulence in a boundary layer on a smooth plane plate with rounded edge (experiment T3H) under a zero pressure gradient was analyzed. Using the well-known experimental and calculated data, the modeling problem of the initially laminar boundary layer transfer to the turbulent one was investigated by the numerical methods on the basis of the near-wall modified turbulence model with two additional transfer equations for the turbulent kinetic energy and the turbulence dissipation rate. Turbulent flows modeling near the flat surface with the high level of incident-flow turbulence is complicated by two general problems: the definition and description of the laminar-to-turbulent transfer along the surface and the viscous sublayer precise resolution under the developed turbulent mode. For the inviscid liquid flowing along the flat plate with the high turbulence degree of more than 1%, the turbulence scale and the incident-flow turbulence intensity joint influence on the flow dynamic and integral characteristics in the boundary layer and turbulence parameters was studied in detail.